Implementasi Model Kepemimpinan Demokratis Kepala Sekolah Dalam Meningkatkan Disiplin Guru Mengajar - HEROSITA, YULIAN (Komunitas Manajemen Kompetitif, 2017)
Abstract: Labor discipline problems teachers provide learning to students is a phenomenon that needs to be addressed. Through the democratic leadership of headmaster attitude is presumably related to discipline the teacher. Using action research methods were implemented school at SDN 023 samples Pandau Jaya and teachers with the implementation of democratic kepemimponan models and descriptive analysis, the obtained results of the research granting school leadership teacher work can improve work discipline teachers in teaching in schools. The data obtained show that once held measuring the level of work discipline teachers through school leadership to work more efficiency, effectiveness, fairness and responsiveness to the application of these cycles affect the teachers' work. This suggests the provision of school leadership work can improve work discipline teachers in teaching in elementary school N 023 Pandau Jaya. Keywords: Democratic leadership model, Discipline Teacher